Parallel germline infiltration of a lentivirus in two Malagasy lemurs. - Clément Gilbert; David G Maxfield; Steven M Goodman; Cédric Feschotte (PLoS Genetics)
Retroviruses normally infect the somatic cells of their host and are transmitted horizontally, i.e., in an exogenous way. Occasionally, however, some retroviruses can also infect and integrate into the genome of germ cells, which may allow for their vertical inheritance and fixation in a given species; a process known as endogenization. Lentiviruses, a group of mammalian retroviruses that includes HIV, are known to infect primates, ruminants, horses, and cats. Unlike many other retroviruses, these viruses have not been demonstrably successful at germline infiltration. Here, we report on the discovery of endogenous lentiviral insertions in seven species of Malagasy lemurs from two different genera -- Cheirogaleus and Microcebus. Combining molecular clock analyses and cross-species screening of orthologous insertions, we show that the presence of this endogenous lentivirus in six species of Microcebus is the result of one endogenization event that occurred about 4.2 million years ago. In addition, we demonstrate that this lentivirus independently infiltrated the germline of Cheirogaleus and that the two endogenization events occurred quasi-simultaneously. Using multiple proviral copies, we derive and characterize an apparently full length and intact consensus for this lentivirus. These results provide evidence that lentiviruses have repeatedly infiltrated the germline of prosimian species and that primates have been exposed to lentiviruses for a much longer time than what can be inferred based on sequence comparison of circulating lentiviruses. The study sets the stage for an unprecedented opportunity to reconstruct an ancestral primate lentivirus and thereby advance our knowledge of host-virus interactions.